Metodologia para a Definição Exigencial de Isolantes Térmicos - Manuel António Pinto da Silva Amaral (1997)
The objective of this work is to propose a certification of prefabricated thermic insulants for the national market and the resulting selection requirements manual. The following procedure was taken to achieve the objectives: the study of a number of certifications existing in the european community; the proposal of a certification for the national market based on the previously studied certifications; the technological specification of the materials which cover buildings in Portugal (a survey was carried out with the "Instituto Nacional de Habitação" - INH (The National Housing Institute; the proposal of a requirements manual based on the previously specification. Four levels of thermic quality for the materials of the buildings are put forward according to the certification presented and based on requirements manual, which may be used as guide lines for a more demanding thermic dimensioning of the materials. A test of its use was carried out and is presented in order to validate the suggested methodology. Lastly, some aspects are referred which may contribute to a swifter acceptance of the certification an the resulting manual.